Artificial Intelligence Solutions for the Disabled - Tripathi, Raghvendra Narain (Indian Journal of Computer Science, 2023)
People with disabilities are often dependent on others to complete their tasks. The healthcare industry has invented many mechanical instruments and aids in the past to make their lives better. The evolution of Artificial Intelligence (AI) has opened up new avenues for improving existing aids like prosthetics and also creating new ones like AI powered apps to help the disabled navigate problems with finding objects, remote controlling them, speech, memory, and dexterity. The present paper covers the problems faced by the disabled and how AI helps them overcomes these.